A dynamically minimalist cognitive explanation of musical preference: is familiarity everything? - Schubert, Emery; Hargreaves, David J.; North, Adrian C. (Frontiers in Psychology, 2014)
This paper examines the idea that attraction to music is generated at a cognitive level through the formation and activation of networks of interlinked ‘nodes’. Although the networks involved are vast, the basic mechanism for activating the links is relatively simple. Two comprehensive cognitive-behavioral models of musical engagement are examined with the aim of identifying the underlying cognitive mechanisms and processes involved in musical experience. A ‘dynamical minimalism’ approach (after Nowak, 2004) is applied to re-interpret musical engagement (listening, performing, composing or imagining any of these) and to revise the latest version of the reciprocal-feedback model (RFM) of music processing. Specifically, a single cognitive mechanism of ‘spreading activation’ through previously associated networks is proposed as a pleasurable outcome of musical engagement. This mechanism underlies the dynamic interaction of the various components of the RFM, and can thereby explain the generation of positive affects in the listener’s musical experience. This includes determinants of that experience stemming from the characteristics of the individual engaging in the musical activity (whether listener, composer, improviser or performer), the situation and contexts (e.g. social factors), and the music (e.g. genre, structural features). The theory calls for new directions for future research, two being (1) further investigation of the components of the RFM to better understand musical experience and (2) more rigorous scrutiny of common findings about the salience of familiarity in musical experience and preference.